2001
DOI: 10.1111/j.1478-4408.2001.tb00068.x
|View full text |Cite
|
Sign up to set email alerts
|

Developing a zero‐AOX shrink‐resist process for wool. Part 1: Preliminary results

Abstract: The efficiency of the proteolytic enzyme papain in conferring shrink-resistance to wool tops and woven fabrics has been enhanced by pretreatment of the wool with lipase/sodium monoperoxyphthalate/ sodium sulphite. This process may be considered as a zero-AOX shrink-proofing treatment. The wool samples treated with this system show excellent shrink-proofed properties. Infrared spectroscopy and Xray photoelectron spectroscopy showed that the Buntë salt together with low concentrations of cystine monoxide and cys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
30
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(30 citation statements)
references
References 9 publications
0
30
0
Order By: Relevance
“…This process may be considered as a zero-absorbable organohalogens (AOX) shrink-proofing treatment [15].…”
Section: Enzymesmentioning
confidence: 99%
“…This process may be considered as a zero-absorbable organohalogens (AOX) shrink-proofing treatment [15].…”
Section: Enzymesmentioning
confidence: 99%
“…Wool properties like handle, lustre and whiteness have been reported to be enhanced by enzyme-catalyzed reactions (Heine and Hö cker 1995;El-Sayed et al 2001) described the use of the protease papain on pre-treated wool (lipase/sodium monoperoxyphthalate/sodium sulphite) resulting in a shrink-proofed effect. A commercial enzyme preparation combined with an alkaline peroxide treatment followed by application of chitosan biopolymer showed good effects concerning shrink resistance of wool, moreover the wettability and whiteness were enhanced (Jovancic et al 2001(Jovancic et al , 2003 showed that during enzymatic treatments the F-layer of wool was completely removed and the content of cysteic acid was significantly decreased whereas during plasma treatment a partial oxidation of hydrocarbon chains of the F-layer and the formation of cysteic acid residues at the wool surface was detected.…”
Section: Introductionmentioning
confidence: 99%
“…The shrink-proofing properties of wool fabrics with an enzymatic treatment were improved. Breier 9 compared the area shrinkage results from the Petry-Lanazym process and from a process using 1.5 g/L Perizym AFW and chlorine with 3% Basolan 10 reported that the efficiency of the proteolytic enzyme papain (EC 3.4.22.2) in conferring shrink resistance to wool tops and woven fabrics was enhanced by the pretreatment of the wool with lipase (EC 3.1.1.3), sodium monoperoxyphthalate (SMPP), and sodium sulfide. A treatment with lipase, SMPP, and sodium sulfide enhanced the efficiency, with respect to the shrink-proofing process, of the subsequent treatments.…”
Section: Introductionmentioning
confidence: 99%
“…El-Sayed et al 12 described an enzyme-based process used to improve the felting resistance of wool top. This process used lipase in the pretreatment step, glutathione reductase in the reduction step, and papain in the posttreatment step.…”
Section: Introductionmentioning
confidence: 99%